Synthesis, Biological Evaluation, and Molecular Simulation of Chalcones and Aurones as Selective Mao-B Inhibitors - Sepulveda-Boza, S; Caroli-Rezende, M; Reyes-Parada, M (Blackwell Publishing Ltd, 2015)
A series of chalcones and aurones were synthesized and evaluated in vitro as monoamine oxidase inhibitors (MAOi). Our results show that aurones, which had not been previously reported as MAOi, are MAO-B inhibitors. Thus, both families inhibited selectively the B isoform of MAO in the micromolar range, offering novel scaffolds for the design of new and potent MAO inhibitors. The main structural requirements for their activity were characterized with the aid of 3D-QSAR and docking studies. © 2014 John Wiley & Sons A/S.